Untethering the widow(er) the case against Article 874 of the Civil Code (Philippine Law Journal, 2022)
The Philippines is no stranger to archaic laws. One such example is Article 874 of the Civil Code of the Philippines, which allows dying spouses, or their ascendants or descendants, to validly impose upon the surviving spouse the condition of non-remarriage in order for them to be entitled to a testamentary disposition.Unlike other outdated laws, however, Article 874 has failed to garner sufficient interest in the past decades to be the subject of debates and, ultimately, reform. This Note hopes to spark such interest by dissecting Article 874 with the goal of uncovering not only bad policy, but constitutionally suspect foundations. By the end, a framework can be set for the legislature or the judiciary to use when revisiting this provision.